2011
DOI: 10.1111/j.2041-1294.2011.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Structure and Properties of Silicon‐Based Oxynitride Glasses

Abstract: The silicon oxynitride glasses take advantage of nitrogen bonding to attain high elastic modulus, increased softening temperatures and viscosities, greater slow crack growth resistance, and modest gains in fracture resistance. Of the oxynitride glasses, the Si–Y–Al‐based oxynitride glasses have been most extensively studied and a degree of success has been achieved in understanding how changes in glass composition affect structural parameters and their relationship with properties. More recent studies have foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
102
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(118 citation statements)
references
References 86 publications
(210 reference statements)
13
102
1
Order By: Relevance
“…It is known that incorporation of nitrogen into any oxide glass network affects the glass properties considerably [23][24][25][26][27][28][29][30][31][32]. Most properties change in the direction that is expected from the increase in the connectivity of the glass network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that incorporation of nitrogen into any oxide glass network affects the glass properties considerably [23][24][25][26][27][28][29][30][31][32]. Most properties change in the direction that is expected from the increase in the connectivity of the glass network.…”
Section: Discussionmentioning
confidence: 99%
“…Studies over the last decades have shown that addition of nitrogen to oxide glasses significantly affects their physical, chemical, mechanical, optical, and thermal properties [23][24][25][26][27]; however, information on the crystallization kinetics and on oxynitride glass-ceramics is scarce. For instance, the glass transition and crystallization temperatures, the elastic moduli, and the lithium mobility increase [28] whereas the thermal 4 expansion coefficient decreases [29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the elastic stiffness of ␤-Lu 2 Si 2 O 7 is higher than that of ␥-Y 2 Si 2 O 7 and ␤-Yb 2 Si 2 O 7 , which may be caused by the stronger bond of Lu O than Y O. Cation field strength (CFS) can be used to represent bond strengths of rare earth silicates. Hampshire proposed that the CFS can be calculated by: CFS = Z c /r c 2 , where Z c is ionic charge of the cation and r c is ionic radius of cation [24,25]. The ionic radius of the lanthanides decreases with increasing atomic number [19,20].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…From their results, the glass-transition temperature of SiYAlON glasses (56Si28Y16Al oxynitride glasses) was found to be in the range of 870 to 950°C, depending on their nitrogen content. 30) In the system 56.5Si44La0.5Y20N80O a maximum glass-transition temperature of around 1020°C was determined. 30) This is significantly lower than the glass-transition temperature for SiLuOC (1291°C) determined here, which will have an impact on the densification behavior of Si 3 N 4 powders and consequently an external pressure during the sintering process should be necessary.…”
Section: Resultsmentioning
confidence: 99%
“…30) In the system 56.5Si44La0.5Y20N80O a maximum glass-transition temperature of around 1020°C was determined. 30) This is significantly lower than the glass-transition temperature for SiLuOC (1291°C) determined here, which will have an impact on the densification behavior of Si 3 N 4 powders and consequently an external pressure during the sintering process should be necessary. A high viscosity of the liquid melt during sintering however provides ¢-Si 3 N 4 particles with high aspect-ratio and improved fracture toughness of the resulting ceramic.…”
Section: Resultsmentioning
confidence: 99%